MOTIVATIONS TO IMPLEMENT SUSTAINABLE WAREHOUSE MANAGEMENT: A LITERATURE REVIEW - Siti Norida Wahab; Sharul Shahida Shakrein Safian; Norashida Othman; Nur Azirah Zahida Mohamad Azhar (International Journal of Accounting, Finance and Business, 2021)
Green supply chain management defines as integrating green and sustainablepractices into supply chain management. Due to the current environmental pollution,companies realized that the concepts of green and sustainability are the focal values towardscreating a competitive advantage. Green and sustainability are also the main values inimplementing sustainable warehouse management (SWM) towards reducing environmentalissues and increasing social responsibility. This conceptual paper aims to observe motivationsto implement SWM because this area is gaining recognition and the findings can be used forfuture research. This paper is based on a comprehensive literature review to discovermotivations to implement SWM. Customer demand, market competition, government support,certification, management support, asset specificity, and information technology are themotivations to implement SWM. This paper only discusses the motivations related to theSWM and ignoring other forms of sustainable practices. Plus, this paper only concerns onEnglish literatures and omits other languages. Due to the lack of empirical evidence, futureresearch should be done to test the motivations relevancy. This study addresses stakeholdersof the SWM, which have not been entirely recognise and acknowledge. This conceptual paperadds value to the knowledge of the SWM and serves as useful information to both scholarsand practitioners.